2016
DOI: 10.1039/c6ib00153j
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the mechano-chemical behaviour of the nuclear pore complex: current research and perspectives

Abstract: This review opens the door to the consideration of how mechanosensing and mechanotransduction can affect the nanomechanics of the NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…In the case of a full blockage of the NPC due to high trafficking and deformation, it therefore allows the ions to open the distal ring and thus, to increase the flux through the NPC. We already mentioned this in a previous paper (Garcia et al, 2016 ) and referenced the works of (Maimon et al, 2012 ; Eibauer et al, 2015 ) which showed such secondary channels.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In the case of a full blockage of the NPC due to high trafficking and deformation, it therefore allows the ions to open the distal ring and thus, to increase the flux through the NPC. We already mentioned this in a previous paper (Garcia et al, 2016 ) and referenced the works of (Maimon et al, 2012 ; Eibauer et al, 2015 ) which showed such secondary channels.…”
Section: Discussionmentioning
confidence: 70%
“…NPCs are a substructure assembly composed of several coaxial rings and 8-fold rotational (Goldberg and Allen, 1996 ; Beck et al, 2004 ; Löschberger et al, 2012 ) symmetrical structures named according to their spatial location: (1) The cytoplasmic ring (CR) and filaments in the cytoplasmic side; (2) The spoke ring (SR) and transmembrane ring, which provide stiffness and stability to the complete NPC, in the nuclear envelop; (3) The nuclear ring (NR), which is attached to the lamina, the nuclear basket, and the distal ring (DR) in the nuclear side. For a detailed description of the structure of the NPC, see the review paper (Garcia et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the direct force propagation via the extracellular matrix–cytoskeleton–nuclear envelope continuum, mechanotransduction also occurs through more indirect ways. For instance, nuclear pore size may be modified in response to nuclear envelope stretching (Garcia et al 2016 ). Alternatively, nuclear membrane may convert tension into biochemical signals, notably by mediating store release of Ca 2+ at the outer nuclear membrane through mechanosensitive ion channels.…”
Section: Conclusion: Avenues For Future Research In Plantsmentioning
confidence: 99%